Pengaruh Penggunaan Bahasa Gaul Terhadap Bahasa Indonesia pada Remaja Milenial - Yuyun Yuliana (Concept: Journal of Social Humanities and Education, 2022)
The existence of a good and correct use of Indonesian has now faded. This is because most teenagers use slang in their daily activities, including in the learning process activities. This study aimed to describe the phenomenon of the influence and impact of the use of slang on the use of Indonesian among adolescents. This research used was literature review method with literature study. The literature search method used was the keywords “Slang”, “Alay Language”, “Impact”, “Indonesian”, “Teenagers”. The data base used for reference in this research is Google Scholar and Portal Garuda.The analysis used was a narrative presented in the form of a description. The use of slang among teenagers has become commonplace and the majority of teenagers use slang in doing their daily activities. The existence of this had an impact on the existence of the decline in the use of Indonesian, difficulty in communicating, affects the way of learning and the learning process. In the learning process, the use of good and correct Indonesian should be emphasized given the many factors that cause the lack of existence of Indonesian.